Strengthening developmental trajectories toward responsiveness: Learning to teach at the middle-level. Issue 5 (20th October 2017) - Pinter, Holly H.; Winter, Kim K.; Strahan, David
Abstract: Many middle level teacher education programs attempt to explicitly address goals such as developmental responsiveness, empowerment and equity. Over the past 3 years, faculty at a regional comprehensive university explored perceptions of professional growth among middle level teacher candidates in a program that attempts to meet these aspirations. Analysis of reflective essays written in response to course assignments have documented ways that participants expressed views of themselves as teachers who reflected the values emphasized during professional courses and internships. Reflecting on internships provided opportunities for participants to analyze classroom experiences using these values as lenses, questioning themselves at times and affirming their values with concrete examples at other times. Insights from this study have guided faculty in designing a developmental framework that scaffolds teacher learning more precisely. Examples from student work provide illustrations of one candidate's learning trajectory.